2011
DOI: 10.1007/s00203-011-0718-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival of thermophilic and hyperthermophilic microorganisms after exposure to UV-C, ionizing radiation and desiccation

Abstract: In this study, we investigated the ability of several (hyper-) thermophilic Archaea and phylogenetically deep-branching thermophilic Bacteria to survive high fluences of monochromatic UV-C (254 nm) and high doses of ionizing radiation, respectively. Nine out of fourteen tested microorganisms showed a surprisingly high tolerance against ionizing radiation, and two species (Aquifex pyrophilus and Ignicoccus hospitalis) were even able to survive 20 kGy. Therefore, these species had a comparable survivability afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 90 publications
(87 reference statements)
2
34
0
Order By: Relevance
“…In general, H. marinus unites some properties which are of essential importance when discussing the past and present habitability of Mars: the organisms can only grow at low oxygen concentrations (down to 0.5 vol % O 2 , Stöhr et al, 2001), the Martian atmosphere contains today an average oxygen concentration of 0.13% (Horneck, 2000); the cells are able to grow in the presence of Martian concentrations of perchlorates in combination with an exceptional desiccation tolerance (Beblo et al, 2009); they are tolerant to salt concentrations up to 1.2 M (Stöhr et al, 2001; Beblo-Vranesevic et al, 2017); the organism shows survival after exposure to UV-C and ionizing radiation (Beblo et al, 2011). The radiation dose rate of ionizing radiation on the surface of Mars was measured and calculated to be up to 0.21 mGy per day (Hassler et al, 2014; Matthiä et al, 2016) and is therefore significantly lower than in the applied experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In general, H. marinus unites some properties which are of essential importance when discussing the past and present habitability of Mars: the organisms can only grow at low oxygen concentrations (down to 0.5 vol % O 2 , Stöhr et al, 2001), the Martian atmosphere contains today an average oxygen concentration of 0.13% (Horneck, 2000); the cells are able to grow in the presence of Martian concentrations of perchlorates in combination with an exceptional desiccation tolerance (Beblo et al, 2009); they are tolerant to salt concentrations up to 1.2 M (Stöhr et al, 2001; Beblo-Vranesevic et al, 2017); the organism shows survival after exposure to UV-C and ionizing radiation (Beblo et al, 2011). The radiation dose rate of ionizing radiation on the surface of Mars was measured and calculated to be up to 0.21 mGy per day (Hassler et al, 2014; Matthiä et al, 2016) and is therefore significantly lower than in the applied experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Theremophilic archaea, including Archaeoglobus and Pyrococcus, tolerate high doses of UV light (25,26), notable given their apparent lack of recognizable lesion repair or bypass mechanisms. UV induces DNA lesions, particularly crosslinks between adjacent pyrimidine bases including: cyclobutane pyrimidine dimers (CPDs) and 6-4 photoproducts (6-4PPs) modifications (27).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would be logical that N. thermophilus is susceptible to both desiccation and ionizing radiation. However, a recent study concluded that there is not a direct correlation between desiccation tolerance and tolerance to radiation among hyperthermophilic archaea (1). It is possible that desiccation or a decrease in water activity in N. thermophilus results in irreversible destabilization and denaturation of intracellular proteins.…”
Section: Desiccation Radiation and Uv Resistance Of The Halophilic mentioning
confidence: 99%